Transcriptomic and Proteomic Analyses of Nepenthes ampullaria and Nepenthes rafflesiana Reveal Parental Molecular Expression in the Pitchers of Their Hybrid, Nepenthes × hookeriana - Zulkapli, Muhammad Mu’izzuddin; Ab Ghani, Nur Syatila; Ting, Tiew Yik; Aizat, Wan Mohd; Goh, Hoe-Han (Frontiers in Plant Science, 2021)
Nepenthes is a genus comprising carnivorous tropical pitcher plants that have evolved trapping organs at the tip of their leaves for nutrient acquisition from insect trapping. Recent studies have applied proteomics approaches to identify proteins in the pitcher fluids for better understanding the carnivory mechanism, but protein identification is hindered by limited species-specific transcriptomes for Nepenthes. In this study, the proteomics informed by transcriptomics (PIT) approach was utilized to identify and compare proteins in the pitcher fluids of Nepenthes ampullaria, Nepenthes rafflesiana, and their hybrid Nepenthes × hookeriana through PacBio isoform sequencing (Iso-Seq) and liquid chromatography-mass spectrometry (LC-MS) proteomic profiling. We generated full-length transcriptomes from all three species of 80,791 consensus isoforms with an average length of 1,692 bp as a reference for protein identification. The comparative analysis found that transcripts and proteins identified in the hybrid N. × hookeriana were more resembling N. rafflesiana, both of which are insectivorous compared with omnivorous N. ampullaria that can derive nutrients from leaf litters. Previously reported hydrolytic proteins were detected, including proteases, glucanases, chitinases, phosphatases, nucleases, peroxidases, lipid transfer protein, thaumatin-like protein, pathogenesis-related protein, and disease resistance proteins. Many new proteins with diverse predicted functions were also identified, such as amylase, invertase, catalase, kinases, ligases, synthases, esterases, transferases, transporters, and transcription factors. Despite the discovery of a few unique enzymes in N. ampullaria, we found no strong evidence of adaptive evolution to produce endogenous enzymes for the breakdown of leaf litter. A more complete picture of digestive fluid protein composition in this study provides important insights on the molecular physiology of pitchers and carnivory mechanism of Nepenthes species with distinct dietary habits.